Relationship with the diaphragm to predict the surgical outcome in large and giant pituitary adenomas - Harel, Ethan; Cossu, Giulia; Daniel, Roy Thomas; Messerer, Mahmoud (Frontiers in Surgery, 2022)
Objective Large and giant pituitary adenomas (L- and G-PAs) continues to remain a surgical challenge. The diaphragm may have a role in determining the shape of the tumor and therefore influencing the extent of resection. The aim of our study is to analyze our surgical series of L- and G-PAs according to their relationship with the diaphragm and invasion of cavernous sinus (CS). Material and methods We performed a retrospective analysis of our surgical series of patients operated for a L- and G-PA. We categorized the tumors according to their relationship with the diaphragm into grade 1 (supradiaphragmatic component with a wide incompetent diaphragm), grade 2 (purely infra-diaphragmatic tumor with a competent diaphragm), grade 3 (dumbbell-shape tumors) and grade 4 (multilobulated tumor with invasion of the subarachnoid space). Results Thirty-seven patients were included in our analysis. . According to our classification, 43.3% patients had grade 1 tumors, 27% of cases were grade 2, 5.4% grade 3 and 24.3% grade 4. CS invasion was confirmed intraoperatively in 17 out of 37 patients (46%). Gross total resection (GTR) was obtained in 19%, near-total resection in 46% and subtotal resection in 35% of cases. All the patients where GTR was achieved, had grade 1 tumors and with the lowest rate of CS invasion (p<0.01). Conclusion Radiological evaluation of the tumor relationship with the diaphragm, invasion of CS and of the subarachnoid space is crucial to plan the surgical strategy and maximize the possibilities of achieving GTR in L- and G-PAs.